Agensi Pastor Paroki dalam Mewujudkan Gereja yang Berjalan Bersama Kaum Miskin - Agus Widodo; Martinus Joko Lelono; Endang Sulastri; Benediktus Tri Widiatmaka; Pius Andi Primanto (Societas Dei: Jurnal Agama dan Masyarakat, 2023)
The Catholic Church is committed to caring for the poor in its efforts to be present in society. In parish life, this is done by managing social funds, including the Dana Papa Miskin (Danpamis). In the Archdiocese of Semarang context, Danpamis is an opportunity to support the poor, the excluded, and those whose dignity is stolen. Even when started with good intentions, carrying out this mission is often ineffective. This study, conducted using quantitative and qualitative methods through questionnaires and in-depth interviews, examines the process of managing Danpamis as an effort by the Church to be more present with the poor. This study focuses on the role of the parish priest as a starting point for understanding the meaning of the Church's presence as a sign of the presence of God, the Savior of the poor. From this study, it becomes clear that the priest's representative role is determined by his personal and spiritual experience in the face of poverty and his awareness of his vocation and mission in the middle of the poor.